The Carrying Capacity of Crop as Cow and Goat Feed in Muna Barat Regency - Musram Abadi; Firman Nasiu; Surahmanto Surahmanto; Abdul Rizal; Fatmawati Fatmawati (Buletin Peternakan, 2019)
This study aimed to assess the potency of forages in Muna Barat Regency as cattle and goat feed. The study was performed by performing forage observation based on the forage production multiplied by the harvested area, and presented on dry matter unit (DM). Sampling was carried out by using a designed square tool. Forages that was evaluated on this study was legume groups. Data analysis was performed by using carrying capacity method. The study reveals that there are 8 types of forages found in Muna Barat Regency. The dry matter of those forages can meet the feed requirement for cattle and goat in Muna Barat Regency. The result of KPRR analysis shows that Muna Barat Regency has carrying capacity for 2,669 cattle and 3,293 goat.